2010
DOI: 10.13005/msri/070215
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational spectra of aniline in gas phase: An ab-initio study

Abstract: Vibrational frequencies of aniline in gas phase have been calculated and each of their modes of vibration assigned properly at RHF and DFT with 6-31G(d) basis set. In the present study, it has been observed that the 6-31G(d) basis set at both RHF and DFT levels of calculations provides better agreement to the experimental findings as compared to other basis sets. Simultaneously, Density functional theory is found to be superior to its counterpart Hartree Fock method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Compared to stable manure application, the addition of vermicompost is more practical and applicable [10], and also it is easier to be transported to the field due to its lesser water content [11]. Furthermore, [12] reported that vermicompost contained N, P, and K nutrients 5 up to 11 times higher than soil. Thus, it could be applied in tobacco cultivation to minimize the use of chemical fertilizer.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to stable manure application, the addition of vermicompost is more practical and applicable [10], and also it is easier to be transported to the field due to its lesser water content [11]. Furthermore, [12] reported that vermicompost contained N, P, and K nutrients 5 up to 11 times higher than soil. Thus, it could be applied in tobacco cultivation to minimize the use of chemical fertilizer.…”
Section: Introductionmentioning
confidence: 99%
“…Around 3 thousand million tonnes of wastes annually produced in India, out of which more than 60% are decomposable (Chauhan et al, 2010). These large quantities of plant residues may serve as potential sources of plant nutrients (Suthar, 2007).…”
Section: Introductionmentioning
confidence: 99%